PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SIGAP DASA PERKASA DI JAKARTA SELATAN - Febriyanto, Erlan; Prasetiyani, Desi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the physical work environment and work discipline on employee performance at PT. Sigap Dasa Perkasa Jakarta Selatan. This research uses a quantitative approach with associative methods. Research data was collected using the questionnaire distribution method, sampling using saturated samples where the sample was determined if 61 members of the population were used as samples. The data analysis used is validity test, reliability test, classical assumption test, multiple linear regression, correlation coefficient, coefficient of determination (R²) and hypothesis testing with Partial Test (t test) and Simultaneous Test (f test). Simultaneous testing obtained a calculated f value > f table or (110.996 > 3.160) with a significance value (sig) of 0.000 < 0.05, thus Ho was rejected and Ha₃ was accepted, meaning that there was a simultaneous and significant influence between the physical work environment and work discipline. on the performance of PT employees. Ready Dasa Perkasa. Strengthened by the R² (R Square) test results obtained at 0.793, it can be concluded that the physical work environment variables (X1) and work discipline (X2) influence the employee performance variable (Y) by 79.3%, while the remainder is (100% - 79.3%) = 20.7% influenced by other factors that were not researched.